Assessment of the mechanical role of cranial sutures in the mammalian skull: Computational biomechanical modelling of the rat skull. (30th January 2023) - Sharp, Alana C.; Dutel, Hugo; Watson, Peter J.; Gröning, Flora; Crumpton, Nick; Fagan, Michael J.; Evans, Susan E.
Abstract: Cranial sutures are fibrocellular joints between the skull bones that are progressively replaced with bone throughout ontogeny, facilitating growth and cranial shape change. This transition from soft tissue to bone is reflected in the biomechanical properties of the craniofacial complex. However, the mechanical significance of cranial sutures has only been explored at a few localised areas within the mammalian skull, and as such our understanding of suture function in overall skull biomechanics is still limited. Here, we sought to determine how the overall strain environment is affected by the complex network of cranial sutures in the mammal skull. We combined two computational biomechanical methods, multibody dynamics analysis and finite element analysis, to simulate biting in a rat skull and compared models with and without cranial sutures. Our results show that including complex sutures in the rat model does not substantially change overall strain gradients across the cranium, particularly strain magnitudes in the bones overlying the brain. However, local variations in strain magnitudes and patterns can be observed in areas close to the sutures. These results show that, during feeding, sutures may be more important in some regions than others. Sutures should therefore be included in models that require accurate local strain magnitudes and patterns of cranial strain, particularly if models are developed for analysis of specific regions, such as the temporomandibular joint or zygomatic arch. Our results suggest that, for mammalian skulls, cranial sutures might be more important for allowing brain expansion during growth than redistributing biting loads across the cranium in adults. Abstract : Cranial bones are connected to each other by sutures. Using the rat cranium as a model system we aimed to investigate how sutures impact bone strain distribution and magnitude during feeding. By combining quantitative dissections and finite element analysis we showed that the presence of sutures does not change the overall cranial bone strain distribution. However, sutures appear to affect the structural behaviour of certain regions of the cranium.